PENGARUH KEADILAN, SISTEM PERPAJAKAN, DISKRIMINASI, KEMUNGKINAN TERJADINYA KECURANGAN, DAN TARIF PAJAK TERHADAP PENGGELAPAN PAJAK (TAX EVASION) - Tyas Ayu Ambarsari, 16.05.62.0042 (Students' Journal of Accounting and Banking, 2019)
This study aims to examine empirically the effect of justice, the taxation system, discrimination, the possibility of fraud, and the tax rate on tax evasion. The sampling technique in this study used a purposive sampling method, with the results of the samples studied were 100 taxpayers at KPP Pratama Semarang Candisari. The data used is primary data with a method of data analysis using multiple linear regression analysis. The results of this study show that the variables of justice, taxation systems, discrimination, the possibility of fraud, and tariffs have a positive and significant effect on tax evasion.Keywords: justice, taxation system, discrimination, the possibility of fraud, tax rates, tax evasio